Haiti : Toward a New Narrative - Singh, Raju Jan; Barton-Dock, Mary (World Bank, Washington, DC, 2015)
This Systematic Country Diagnostic seeks to identify the most important constraints to and opportunities for inclusive and sustainable growth in Haiti, a country that is one of the poorest and least equal countries in the world. For this purpose, an extensive review of the literature (from both within and outside the World Bank) was carried out, as well as broad consultations across the country. The results point out five broad themes around which activities need to be organized in order to ignite a process whereby Haiti could set itself on a new development path: (i) balancing macroeconomic stability with developmental needs; (ii) improving statistics and analytics; (iii) creating greater economic opportunities and better jobs, including through infrastructure and human capital; (iv) (re)building the social contract; and (v) reducing vulnerabilities and building resilience. Progress on all these themes is needed simultaneously. In light of the tighter budget constraints facing the government, maintaining the stability of the macroeconomic environment, and improving knowledge and statistics to increase the effectiveness of public policy (including more transparent fiscal reporting) call more particularly for immediate attention.